Providing material samples for the structure construction, pre-opening and pre-embedding works of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding material samples for the structure construction, pre-opening and pre-embedding works of BRAC University new campus project.